PERBEDAAN KARAKTERISTIK KIMIA DAN DAYA CERNA PATI TEPUNG JAGUNG DAN TEPUNG KECAMBAH JAGUNG (Zea mays L.) - Kurniawan Lombu, Willem; Wisaniyasa, Ni Wayan; Sri Wiadnyani, AAI. (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 7 No 1 (2018): Jurnal ITEPA, 2018)
This study aims to determine the difference of characteristic and starch digestibility of germinated and ungerminated flour. This study used randomized complete design (RCD) three repeated. The corn germinated for 36 hours. Corn germinated flour and ungerminated flour were evaluated directly of the chemical composition of the flour content, moisture content, ash content, protein, fat, carbohydrates, fiber, starch content and starch digestibility. The results showed the corn germinated flour has increased of moisture content from 9.66% into 10.38%, increased of protein into 7.22% into 8.45%, increased of fiber content from 2.28% into 2.79% and increased of starch digestibility from 57.04% into 62.43%. While were the decreased fat content from 5.17% into 4.76%, decreased of carbohydrate from 75.41% into 73.89% and decreased of starch content from 76.10% into 69.40%. The treatmented has no effect for the flour content decreased from 41.40% into 40.36% and ash content decreased from 2.52% into 2.51%. Germinated increased starch digestibility and changed the character of corn flour.